2006
DOI: 10.1021/jm060137l
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Novel Sulfonamide-Containing Bradykinin hB2 Receptor Antagonists. 1. Synthesis and SAR of α,α-Dimethylglycine Sulfonamides

Abstract: We recently published the extensive in vivo pharmacological characterization of MEN 16132 (J. Pharmacol. Exp. Ther. 2005, 616-623; Eur. J. Pharmacol. 2005, 528, 7), a member of the sulfonamide-containing human B(2) receptor (hB(2)R) antagonists. Here we report, in detail, how this family of compounds was designed, synthesized, and optimized to provide a group of products with subnanomolar affinity for the hB(2)R and high in vivo potency after topical administration to the respiratory tract. The series was desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
(51 reference statements)
0
8
0
Order By: Relevance
“…Using mutagenesis of the human B 2 receptor, we previously presented data on the essential role of the quinoline moiety of non‐peptide antagonists and its interaction with some residues belonging to TM3, TM6 and TM7 (Meini et al ., 2004), which together define a lipophilic receptor binding crevice in a part of the receptor involved in the balance of active/inactive protein conformers, either for the human B 2 receptor or other GPCRs (Gether and Kobilka, 1998; Marie et al ., 2001; Rosenbaum et al ., 2009). In this study, our efforts are focused on finding specific receptor counterparts for the other pharmacophores of MEN16132, such as the tetrahydropyranyl and the quaternary ammonium groups, which were known to be important for high affinity ligand–receptor interaction from structure–activity relationship studies (Fattori et al ., 2006; 2007). The W86 residue was identified as being involved both in the binding interaction of agonist and other non‐peptide antagonists besides MEN16132 (Meini et al ., 2002; Bellucci et al ., 2003), but not peptide antagonists such as icatibant or MEN11270 (this study; Meini et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using mutagenesis of the human B 2 receptor, we previously presented data on the essential role of the quinoline moiety of non‐peptide antagonists and its interaction with some residues belonging to TM3, TM6 and TM7 (Meini et al ., 2004), which together define a lipophilic receptor binding crevice in a part of the receptor involved in the balance of active/inactive protein conformers, either for the human B 2 receptor or other GPCRs (Gether and Kobilka, 1998; Marie et al ., 2001; Rosenbaum et al ., 2009). In this study, our efforts are focused on finding specific receptor counterparts for the other pharmacophores of MEN16132, such as the tetrahydropyranyl and the quaternary ammonium groups, which were known to be important for high affinity ligand–receptor interaction from structure–activity relationship studies (Fattori et al ., 2006; 2007). The W86 residue was identified as being involved both in the binding interaction of agonist and other non‐peptide antagonists besides MEN16132 (Meini et al ., 2002; Bellucci et al ., 2003), but not peptide antagonists such as icatibant or MEN11270 (this study; Meini et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Present data obtained from the wild type receptor cell system indicate that MEN16132 displays an even higher antagonist potency also towards the B 2 receptor activation mediated by the non‐peptide agonist FR190997 (pA 2 9.1–9.6). We consider the reduction of potency and the minor insurmountable antagonist behaviour observed with MEN16132 at the D266A/D284A B 2 receptor mutant, as indicative of an interaction of these residues with the basic quaternary ammonium group, previously shown to contribute to the high antagonist potency of this compound (Fattori et al ., 2006; 2007) (Figure 6). The difference observed at the mutant D266A/D284A receptor is not as great as that previously observed with icatibant (see above), and we consider that this is due to the buried interaction of MEN16132 within the TM receptor region provided by TM3, 6 and 7 (see above) and to the fact that FR190997 interacts with some residues (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In this paper we have described the extensive work carried out on MEN 15422, the lead compound from our first paper. 11 Changes to the amino acid used to form the central sulfonamide unit and to the nature and distribution of the polar groups in the terminal chain produced a compound, MEN 16132 (72), which was 100× more active in vivo. This new molecule, when administered locally, was a potent and long lasting antagonist of BK-induced bronchoconstriction in the airways, devoid of any significant effects on BK-induced hypotension.…”
Section: Discussionmentioning
confidence: 99%
“…The compounds described in this study are shown in Tables 1-3, and the synthetic methods for their preparation are outlined in Schemes 1-7. Chlorosulfonic acid 1 11 was subjected to radical bromination under standard conditions (NBS, AIBN) to obtain benzylbromide 2. Formation of the sulfonamides with the corresponding R,R-aminoacids was performed in two ways, either via a classical base-catalyzed reaction with the amino acid methyl ester or by the addition of the amino acid pretreated with BSA (N,O-bis-trimethylsilylacetamide).…”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation